1993
DOI: 10.1016/0735-1097(93)90373-9
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous dobutamine stress echocardiography and technetium-99m isonitrile single-photon emission computed tomography in patients with suspected coronary artery disease

Abstract: Dobutamine stress echocardiography represents a reasonable alternative to dobutamine mibi SPECT for the functional assessment of patients with suspected myocardial ischemia and without previous myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
1

Year Published

1994
1994
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(40 citation statements)
references
References 23 publications
3
36
0
1
Order By: Relevance
“…[20][21][22][23][24][25][26][27] Similarly, our results are comparable to those from studies using the dual-isotope protocol, which reportedly has a sensitivity of 90-96% and specificity of 73-92%. 7,28,29 In our protocol, the average total examination time was less than 110 min, which is comparable to that for the dualisotope protocol.…”
Section: Discussionsupporting
confidence: 79%
“…[20][21][22][23][24][25][26][27] Similarly, our results are comparable to those from studies using the dual-isotope protocol, which reportedly has a sensitivity of 90-96% and specificity of 73-92%. 7,28,29 In our protocol, the average total examination time was less than 110 min, which is comparable to that for the dualisotope protocol.…”
Section: Discussionsupporting
confidence: 79%
“…2 The same phenomenon has been postulated for demand ischemia to explain the higher sensitivity of perfusion abnormalities over inducible regional dysfunction and the higher prevalence of both over an abnormal ECG and angina during stress testing. [3][4][5][6][7][8] There is, however, no direct evidence to support this notion in a rigorous experimental setting where perfusion and function have been evaluated simultaneously. Furthermore, a comparison of this phenomenon has not been performed in models of single-vessel stenosis (SVS) versus multivessel stenosis (MVS).…”
mentioning
confidence: 91%
“…17,[26][27][28] The lower specificity of SCINT in our investigation is attributable to the false positive results associated with mild coronary stenosis, left bundle-branch block, and left ventricular hypertrophy as has been reflected in previous reports. [28][29][30] It has been reported that diagnostic accuracy of SPECT analysis is lower in women than in men and is probably related to a smaller left ventricular chamber size in women. 31 With these considerations in mind, SCINT can be advocated in the diagnosis of CAD in women after excluding subgroups known to decrease specificity.…”
Section: Discussionmentioning
confidence: 63%